Treatment of Tourette Syndrome With Attention Training Technique—A Case Series - Schaich, Anja; Brandt, Valerie; Senft, Alena; Schiemenz, Christian; Klein, Jan-Philipp; Faßbinder, Eva; Münchau, Alexander; Alvarez-Fischer, Daniel (Frontiers in Psychiatry, 2020)
The existing therapeutic strategies of Tourette syndrome (TS) do not lead to sufficient improvement in a significant number of patients. Recently published studies show that paying attention to tics increases whereas directing attention away decreases tic frequency. The aim of the present case series in three patients with TS was to investigate the effect of Attention Training Technique (ATT), a technique derived from metacognitive therapy that aims on training patients to consciously (re-)focus their attention away from themselves, on TS symptoms. Friedman’s chi-square test indicated a trend regarding the reduction of tic frequency and tic severity and a significant reduction of positive metacognitions from pre-baseline to follow-up. Reliable Change Indices (RCIs) are given for each measure and patient. Given the small number of patients, further studies including randomized controlled trials appear warranted.